STRATEGI PENGEMBANGAN BATIK BERBASIS EKONOMI KREATIF KAMPUNG BATIK KAUMAN PEKALONGAN - Listiyaningrum, Anita; Rustiana, Ade; Saeroji, Ahmad (Business and Accounting Education Journal, 2020)
The purpose of this study was to determine the strategy of developing batik business in an effort to improve the competitiveness of the Kauman Batik Village community. This study uses qualitative methods with SWOT analysis. In this study, researcher conducted interviews with the activists of the creative economy with the quadruple helix concept, namely the participation of academics, government, communities and business people. From the SWOT analysis, it was obtained the results that the aspect of the resource needs the next generation of batik who have good creativity. The second aspect is industry. A thing that is being an important role of the industry is raw materials;it is needed to ease the production process. The third aspect is marketing. Batik producer needs to expand the market for batik sales. Then, the fourth aspect is financial. Batik producer needs to regulate the business finances in detail. The fifth aspect is technology and infrastructure; namely the need for infrastructure to support the development of the Kauman Batik Village. The advice given to Kauman Batik Village Community in overcome these five aspects which need participation from the government and private sector, communities and academics. In hope the government will optimize the work program in supporting batik as the superior product of Pekalongan City.